Revisiting the rules for anatomical targeting of ventralis intermediate nucleus. (October 2019) - Nowacki, Andreas; Bogdanovic, Marko; Sarangmat, Nagaraja; Fitzgerald, James; Green, Alex; Aziz, Tipu Z.
Highlights: A simple and reproducible targeting technique for VIM is presented. Width of third ventricle and laterality of VIM position are positively correlated. Adaptation of laterality according to third ventricular width leads to accurate targeting. Abstract: Indirect targeting of the Ventralis Intermedius Nucleus (Vim) is widely used for functional neurosurgical procedures to treat essential tremor (ET). Here, we review if the laterality of the Vim depends on the diameter of the third ventricle and if a targeting approach that incorporates this correlation can facilitate targeting and yields accurate lead placement. We analyzed 15 consecutive ET patients. Vim targeting was adapted according to the width of the third ventricle and the lateral distance to the internal capsule (IC). Postoperative outcome was assessed 12 months post-OP based on the Bain-Findley score. Application of this targeting approach resulted in mean target coordinates of LAT 12.8 ± 1.5; AP −3.6 ± 1.0 and VERT 0 ± 0 mm and which projected onto the Vim. The laterality of IC and Vim are correlated to the width of the third ventricle. The mean postoperative tremor reduction was 63.0%. In summary, adjusting the lateral coordinate according to the width of the third ventricle leads to accurate targeting and effective tremor reduction.